1982
DOI: 10.1172/jci110477
|View full text |Cite
|
Sign up to set email alerts
|

Glucose ingestion in dogs alters the hepatic extraction of insulin. In vivo evidence for a relationship between biologic action and extraction of insulin.

Abstract: A B S T R A C T Oral glucose (25 g) fed to seven healthy, conscious dogs resulted in an increase in peripheral plasma glucose from 109±3 to 178±10 mg/dl. Concurrently serum insulin increased in the portal vein to levels approximately threefold greater than those in the periphery. Hepatic insulin delivery rose from 10.8±0.7 to 59.0±19.9 mU/min at 60 min, coincident with an increased hepatic insulin extraction from 3.3 to 41.4 mU/min (corresponding to an increase in hepatic extraction from 31±4 to 59±7%), both r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 49 publications
1
38
0
Order By: Relevance
“…Reasons for this may include the fact that C-peptide and insulin antibodies have no cross-reaction [20] and that it does not undergo significant hepatic extraction [21,22]. Note, the liver is the major site of insulin metabolism, variably extracting ~50% of insulin delivered to it [23][24][25]. It has therefore been suggested that peripheral C-peptide levels more accurately reflect pancreatic insulin secretion rates than do peripheral insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this may include the fact that C-peptide and insulin antibodies have no cross-reaction [20] and that it does not undergo significant hepatic extraction [21,22]. Note, the liver is the major site of insulin metabolism, variably extracting ~50% of insulin delivered to it [23][24][25]. It has therefore been suggested that peripheral C-peptide levels more accurately reflect pancreatic insulin secretion rates than do peripheral insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kawamori et al and other researchers have pointed out that plasma insulin concentrations of peripheral veins do not serve as an indicator of insulin secretion from the pancreas based on the results of insulin kinetics and metabolism studies using normal fasting dogs. [14][15][16] In addition, venous plasma insulin concentrations after having passed through the liver have been indicated as being 50% or less of concentrations in the portal vein. 17,18) In other words, the control of blood glucose levels is thought to take place based on insulin concentration in the portal vein and not in the peripheral blood.…”
Section: Plasma Nateglinide Concentration Plasma Insulin Concentratimentioning
confidence: 99%
“…All subjects were within 10% of ideal body weight. The diabetic patients were insulin-dependent with a disease duration of 9.4±2.3 yr (range, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. None had clinically significant vascular, renal, eye, or neurological complications.…”
Section: Subjectsmentioning
confidence: 99%
“…The rationale for this approach depends on the fact that the liver is the major site of insulin metabolism, variably extracting -50% of insulin delivered to it (6)(7)(8)(9)(10)(11). C-peptide is Receivedfor publication 25 June 1985 and in revisedform 28 August 1985. cosecreted from the beta cell on an equimolar basis with insulin (12) but does not undergo significant hepatic extraction (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%